PEMBELAJARAN SEJARAH KEBUDAYAAN DI MADRASAH ALIYAH: KONSEP, INDIKATOR, MATERI DAN EVALUASI - Hajizah, Hajizah; Noorazmah Hidayati (STAI Nurul Falah Airmolek, 2023)
SKI learning is one of the contents of Islamic Religious Education subjects which is directed to recognize, understand, and appreciate Islamic history, which then becomes the basis for students' worldview (way of life) through teaching, guidance, exemplary, practice, habituation and experience. SKI learning is usually implemented at educational levels such as at the MI, MTs, and MA levels, where the material taught in SKI includes a broad context of Islamic cultural history with learning practices based on approaches that are in accordance with the development of students. In SKI learning, it must use the right approach in understanding historical events which contain values that can be applied in everyday life. The presentation of SKI material must also consider learning objectives and graduate competency standards, so that SKI learning in the classroom can be more enjoyable, generate critical thinking, and can develop personalities in accordance with SKI values in students. Furthermore, the evaluation of SKI learning is carried out on an ongoing basis so that the quality of learning can be continuously improved by balancing the knowledge, attitude, and psychomotor aspects of students. Keywords: SKI, Islamic Religious Education, Materials, Evaluation.